Development of shrimp shells-based compost and plant-based pesticide using bio-activators from Golden Apple Snails and their effects on the kenaf plant growth and pest population - RUSMINI RUSMINI; RIAMA RITA MANULLANG; DARYONO DARYONO (Nusantara Bioscience, 2017)
Rusmini, Manullang RR, Daryono. 2017. Development of shrimp shells-based compost and plant-based pesticide using bioactivators from Golden Apple Snails and their effects on the kenaf plant growth and pest population. Nusantara Bioscience 9: 260-267. Kenaf (Hibiscus cannabinus L) cultivation generally uses chemical fertilizers and pesticides to increase production despite the adverse effects of those chemicals toward environmental ecosystem. Meanwhile, there are a lot of unutilized wastes produced from agriculture and fishery. This study aimed to develop the best bio-activator from Golden Apple Snails and spices to decompose the shrimp shells waste. The bioactivator was utilized for the production of plant-based pesticide to control pests in kenaf plant, and shrimps-shells-based composts to improve kenaf plant growth. This study employed a Randomized Block Design with two factorials. The first factor was the shrimp shells-based composts (K) which consist of three levels, and the second factor was the plant-based pesticide (P) which also consists of three levels. Each of experiment was repeated twice. Thus, in total there were 18 treatments. The shrimp shells-based composts had a pH value of 8.79, Potassium (K) 8.13 %, organic carbon (C) 17.45%, Nitrogen (N) 3.62%, Phosphorus (P) 2.27%; Magnesium (Mg) 0.59%, and Calcium (Ca) 7.64%; and a C/N ratio of 4.82. Kenaf plant height at 6 and 9 weeks after planting (WAP) showed significant differences upon the shrimp shells-based composts treatments. At 6 weeks after planting, kenaf plant diameter showed significant differences upon the composts treatment, while at 9 weeks after planting, the plant diameter indicated significant differences upon both the compost and plant-based pesticide applications. Pest populations that were present in kenaf plants were caterpillars, bugs, and beetles.